The Effect of Vocabulary Depth and Breadth on English Listening Comprehension Can Depend on How Comprehension Is Measured - Luo, Yuzhi; Song, Hongwen; Wan, Li; Zhang, Xiaochu (Frontiers in Psychology, 2021)
This study examined the relative contribution of vocabulary breadth and vocabulary depth to three different listening comprehension measures. One hundred and thirteen English majors were given a vocabulary breadth test, a vocabulary depth test and three listening comprehension tests. Based on three pairs of hierarchical multiple regression analyses, we found that the relative contribution of vocabulary depth and breadth varied across these three listening comprehension tests. Specifically, for the listening test with an expository text dictation assessing integrative skills, both vocabulary breadth and depth made unique positive contribution to comprehension, but this was greater in the case of depth. For the listening test involving narrative conversations assessing literal comprehension, neither vocabulary breadth nor depth (after controlling for each other) could independently predict comprehension, whereas for the listening test comprising expository passages assessing inferential comprehension, vocabulary depth could separately predict comprehension, but vocabulary breadth could not. These findings suggest that the relative contribution of vocabulary depth and breadth to listening comprehension may depend on how a listening test is constructed. Therefore, our findings will contribute to listening comprehension and vocabulary knowledge research, and vocabulary teaching and learning as well.